Analisis Frekuensi Alami dengan Undamped-Degree of Freedom System pada Jembatan Sei Wampu - Ainil Mardhiyah; Johannes Tarigan; Emma Patricia Bangun (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Natural frequency is one of the factors in bridge construction. Because the natural frequency can be used as an indicator to detect the ability of the bridge, including the ability to withstand resonance. In addition, the natural frequency is also a way to analyze damage that will or has already occurred to a bridge. One of the analytical methods that can be used to analyze natural frequency values is the Undamped-Degree of Freedom. The results of this study indicate that the natural frequency value of the Sei Wampu Bridge has a value of 10.97 rad/s for the first mode, 18.06 rad/sec for the second ,mode and 20.34 rad/sec for the third mode. From the results of this analysis, it can be seen that the natural frequency value will increase as the bridge mode increases.